THE ROLE OF TECHNOLOGY AND ETHICS IN SHAPEING HUMANITY'S DIGITAL FUTURE - Aini, Farida Nurul; Zamroni, Zamroni; Solekhin, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Digital transformation has brought about major changes in human life, from how we interact to data-driven decision-making. However, the rapid pace of technological innovation raises various ethical challenges that require attention, such as privacy, fairness, and social responsibility. This study examines the role of technology and ethics in shaping the digital future of humanity, using a descriptive-analytical approach based on relevant academic literature. This study highlights the importance of integrating ethical frameworks in technology development to ensure a positive impact on global society.